Barriers and Facilitators of Health Care Services at the Time of Natural Disasters - Hamid Reza Khankeh; Rakhshandeh Mohammadi; Fazlollah Ahmadi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: Tragic impacts of natural disasters, because of interrupting normal life process, widespread mortality, injuries, massive social disruptions and generating a lot of human needs such as first aid and medical services, have to be managed strongly and coordinated by the high executive managers and organizations. The most important factor in saving human lives is delivering effective health care at the early stages of natural disasters. Since natural disasters have so many prominent effects on public health and welfare, then assessing barriers and facilitators of health care services at the time of natural disasters are in great concerns. In this paper we tried to assess the mentioned factors of health care services at the time of disaster based on the experiences of health care providers. Materials & Methods: The present study was conducted by grounded theory. 14 participants consist of 4 nurses, 1 social worker, 1 psychologist, 2 psychiatrists, 1 general physician, 1 health professional, 1 epidemiologist and 2 city of Bam residents. Semi structural interviews were used for data gathering. All of the interviews were transcribed verbatim (word for word) and simultaneously constant comparative analysis was used according to Strauss and Corbin method. Results: Through data analysis, several main themes emerged to describe the factors that hindered or facilitated health care services at the time of disasters. The study participants mentioned several main factors such as human factors, coordination, equipments, management, Informational and cultural factors through the codes like, lack of professions, coordination, personnel, equipments, information broadcasting, self centrism and so on as barriers, and management services, cultural and educational factors, human resources and equipments in several codes like management unity, necessity of coordination, importance of victims transportation and cultural issues, presence of general physician and nurses, human needs meeting based on culture and so on as facilitators at the time of natural disasters. Conclusion: The participants in this study, believed that lack of coordination in management, human resources, equipments and information broadcasting were the most significant barrier of health care services at the time of disasters and delivering efficient, fast and qualified services is possible then if the work done coordinately and through a process which includes fast assessment of the location, announcing and dispatching the groups, information gathering and broadcasting and continuous evaluating these actions.